2020
DOI: 10.1503/cjs.000319
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the utility of computed tomography of the chest for gastric cancer staging

Abstract: Evaluating the utility of computed tomography of the chest for gastric cancer staging Background: International guidelines recommend routine computed tomography (CT) of the chest for gastric cancer staging. In Asian countries, where the incidence of pulmonary metastases is less than 1%, some guidelines recommend chest CT only for gastroesophageal junction cancers. If the incidence of pulmonary metastases is also low in Canada, routine chest CT may not be beneficial. Methods: We performed a retrospective review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Similarly, for regular microvessels, mucosal capillaries show a uniform shape, closed loop, or open; for irregular microvascular structure, microvessels show open, closed loop, twisted, branched, and other shapes, with different shapes. Uniform, asymmetric distribution, and irregular arrangement; missing microvessels, manifested as the disappearance of microvascular structures, are replaced by white opaque substances [ 14 , 15 ]. According to the “VS classification system,” early gastric cancer can be diagnosed if any of the following is satisfied; otherwise, it is a non-cancerous lesion: (1) irregular surface microstructure (IMSP) and clear demarcation line (DL); (2) irregular Microvessels (IMVP) and specific lines of differentiation (DL) [ 16 ].…”
Section: Research On the Diagnosis Of Early Gastric Cancer Based On M...mentioning
confidence: 99%
“…Similarly, for regular microvessels, mucosal capillaries show a uniform shape, closed loop, or open; for irregular microvascular structure, microvessels show open, closed loop, twisted, branched, and other shapes, with different shapes. Uniform, asymmetric distribution, and irregular arrangement; missing microvessels, manifested as the disappearance of microvascular structures, are replaced by white opaque substances [ 14 , 15 ]. According to the “VS classification system,” early gastric cancer can be diagnosed if any of the following is satisfied; otherwise, it is a non-cancerous lesion: (1) irregular surface microstructure (IMSP) and clear demarcation line (DL); (2) irregular Microvessels (IMVP) and specific lines of differentiation (DL) [ 16 ].…”
Section: Research On the Diagnosis Of Early Gastric Cancer Based On M...mentioning
confidence: 99%
“…In a retrospective study, our group previously found an incidence of pulmonary metastases of 5.4%. 37 …”
Section: Discussionmentioning
confidence: 99%
“…In a retro spective study, our group previously found an inci dence of pulmonary metastases of 5.4%. 37 In a landmark study from Memorial Sloan Kettering Cancer Center in 1997, Burke and colleagues demon strated that staging laparoscopy spared 24 of 111 patients with gastric cancer the morbidity associated with under going a full laparotomy, as these patients were found to have M1 disease at laparoscopy that was not visible with other preoperative staging modalities. 38 Current guide lines in Alberta recommend that staging laparoscopy be considered for all patients with potentially resectable GEA.…”
Section: Discussionmentioning
confidence: 99%